2008
DOI: 10.1021/jp076467e
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of Ionic Liquids [Cnmim]Br (n = 4, 6, 8, 10, 12) in D2O:  A NMR Study

Abstract: Aqueous solutions of five ionic liquids (ILs) of the 1-n-alkyl-3-methylimidazolium bromide family, [C(n)mim]Br (n = 4, 6, 8, 10, 12), were investigated by NMR measurements at 298.2 K as a function of IL concentrations. Critical aggregation concentrations and aggregation numbers of these ILs were determined by 1H NMR except for [C4mim]Br in D2O. The effects of the alkyl chain length of the cations were examined on the aggregation behavior of the ILs. 1H NMR data of the solvent D2O were used to investigate the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
197
3
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(223 citation statements)
references
References 44 publications
21
197
3
2
Order By: Relevance
“…A similar observation has been previously reported for N-dodecyl-N,N-dimethyl-N-benzylammonium chloride in D 2 O, [19] and for 1-methyl-3-octylimidazolium bromide in D 2 O. [20] The presence of these cross-peaks seems to indicate that, at 298 K, the liquid structure of geminal IL 1 is governed not only by Coulomb interactions, but also by p-p stacking between imidazolium and the phenyl ring. The p-p interactions between aromatic motifs are well known.…”
Section: Nmr Spectroscopy Measurementssupporting
confidence: 86%
“…A similar observation has been previously reported for N-dodecyl-N,N-dimethyl-N-benzylammonium chloride in D 2 O, [19] and for 1-methyl-3-octylimidazolium bromide in D 2 O. [20] The presence of these cross-peaks seems to indicate that, at 298 K, the liquid structure of geminal IL 1 is governed not only by Coulomb interactions, but also by p-p stacking between imidazolium and the phenyl ring. The p-p interactions between aromatic motifs are well known.…”
Section: Nmr Spectroscopy Measurementssupporting
confidence: 86%
“…Rollet et al demonstrated : 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, the existence of water molecules in the phase-separated IL aggregates on the microscopic scale changes the self-diffusion coefficients of each species. [23] In a similar manner to that report by Wang et al, [24] a characteristic shape of the plot of concentration versus chemical shift proves the emergence of conduction paths consisting of ZILs (see Figure S5, Supporting Information). The chemical compositions of IL and water are critical for formation of proton conduction networks.…”
supporting
confidence: 82%
“…ILs are designed to be chaotropic, and, thus, the aqueous and solution chemistries are only sparingly explored (42). Recent molecular dynamics simulation studies (43)(44)(45), as well as spectroscopic investigation via NMR techniques (46,47), suggest that ILs do not dissolve as independent ions but keep a nanostructured organization in aqueous media. After all, the inherent properties of ILs are not like traditional crystalline salts, and the very properties that make ILs low melting also make them behave differently both in the melt and in solution.…”
Section: Ion-pair Based Transportmentioning
confidence: 99%